Applications of Public Deliberation: Themes Emerging fromTwelve Personal Experiences Emanating from National Issues Forums Training - Renée A. Daugherty; Sue E. Williams (Journal of Deliberative Democracy, 2007)
In order to learn about post-training efforts in public deliberation in Oklahoma, a study was conducted with individuals who had completed a two-day course to become conveners, moderators, and recorders of deliberative forums. In Phase Two of the study (the qualitative portion), twelve individuals participated in in-depth personal interviews to describe a personal experience of significance related to public deliberation. The audio-recorded interviews were transcribed and analyzed. Five themes emerged from the data analysis: variety of settings; examination of benefits and consequences; use of guidelines and forum rules; common ground for the public good; and deliberative leadership. Study findings reinforced the use of some methodologies used in the two-day course and led to recommendations for post-course training and mentoring.